Bleeding oesophageal varices with long term follow up. Issue 4 (April 1984) - Spence, R A; Johnston, G W; Odling-Smee, G W; Rodgers, H W
Abstract : Complete long term follow up was obtained in 27 children who had bled from oesophageal varices. Most presented with haematemesis or melaena at an average age of 5.2 years in the portal vein thrombosis group (20 children) and 9.5 years in the intrahepatic group (7 children). All had splenomegaly. Only 6 of 20 children with portal vein thrombosis had a possible precipitating factor. A total of 182 admissions for bleeding are reported, in 68 of which injection sclerotherapy was used to control bleeding. Control rate with injection sclerotherapy was 97%. Shunts performed below age 10 years were associated with a high thrombosis rate. A conservative approach to bleeding varices in children is recommended with transfusion, pitressin, and injection sclerotherapy. Oesophageal transection may have a role in the emergency management of the few children in whom bleeding is not controlled by injection sclerotherapy.